Histomorphometric analysis of the repair process of autogenous bone grafts fixed at rat calvaria with cyanoacrylate - Esteves, Jonatas Caldeira [UNESP]; Borrasca, Albanir Gabriel; Aranega, Alessandra Marcondes [UNESP]; Garcia Junior, Idelmo Rangel [UNESP]; Magro Filho, Osvaldo [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2011)
Objective: The purpose of this study was to perform histological and histometric analyses of the repair process of autogenous bone grafts fixed at rat calvaria with ethyl-cyanoacrylate adhesive. Material and Methods: Thirty-two rats were divided into two groups (n=16), Group I - Control and Group II - Adhesive. Osteotomies were made at the right parietal bone for graft obtainment using a 4-mm-diameter trephine drill. Then, the bone segments were fixed with the adhesive in the parietal region of the opposite side to the donor site. After 10 and 30 days, 8 animals of each group were euthanized and the calvarias were laboratorially processed for obtaining hematoxylin and eosin-stained slides for histological and histometric analyses. Results: An intense inflammatory reaction was observed at the 10-day period. At 30 days, this reaction was less intense, despite the presence of adhesive at the recipient-site/graft interface. Graft incorporation to the recipient site was observed only at the control group, which maintained the highest graft size at 10 and 30 days. Conclusions: Although the fragment was stable, the presence of adhesive in Group II did not allow graft incorporation to the recipient site, determining a localized, discrete and persistent inflammatory reaction.
Keywords: Tissue adhesives; Cyanoacrylates; Bone transplantation